Collaborative governance at the Malabot Tumbe Festival in Banggai Laut, Indonesia - Ruslan, Ruslan; Hijjang, Pawennari; Kembara, Jayana Suryana (CENDERAWASIH: Jurnal Antropologi Papua, 2025)
This research aims to determine and analyze the forms, parties involved, and challenges faced in implementing collaborative governance in the Malabot Tumbe Festival activities in Banggai Laut Regency, Indonesia. This study uses a descriptive qualitative approach, with 10 informants, with a research location in Banggai Laut Regency, Central Sulawesi Province, Indonesia, carried out on July 10-17, 2024. The study results show that the Malabot Tumbe Festival in Banggai Laut Regency reflects the success of cross-sector collaboration in preserving local culture through a collaborative governance approach. Local governments, indigenous leaders, communities, the private sector, and the media work together to ensure the continuity of this tradition. Key factors include trust, effective communication, visionary leadership, and resource support. However, challenges such as differences in interests, budget limitations, and lack of participation of certain groups remain. With continuous evaluation, this festival positively impacts cultural preservation, economic empowerment, and tourism and strengthens the community's collective identity, making it an example of success in cultural and regional development.